Mission Impossible: International Students as Key Players in Cross-Cultural Team Activities - Ranson, Heather (Journal of International Students, 2018)
An annual undergraduate project called Mission Impossible is designed to reduce issues of power and status that hinder the effectiveness of cross-cultural teams. Domestic students often think they must compensate for international teammates, and international students understand that they are seen as a burden by domestic teammates. To prevent students from falling into this common but damaging dynamic, this undergraduate full-day event is designed to help international and domestic students engage as equals. This sets the stage to allow collaborative relationships to deepen between domestic and international students in the rest of the program.